THE EMERGENCE OF DAY OF THE WEEK EFFECT IN THE INDIAN NIFTY ENERGY SECTOR: ANALYSIS AND INTERPRETATIONS - Sanganeria, Drishti; Maheswari, Raghav (Journal of Advance Research in Business, Management and Accounting (ISSN: 2456-3544), 2024)
This study delves into the presence and evolution of the day-of-the-week effect within the Indian NIFTY Energy Sectoral Index.  Employing a comprehensive dataset of daily returns spanning the years 2005 to 2023, the analysis is segmented into two distinct time periods: 2005-2015 and 2016-2023.  This segmentation allows for a granular examination of potential shifts in the nature or intensity of calendar anomalies within this market segment.Findings from the initial period (2005-2015) reveal the absence of statistically significant day of-the-week effects. This aligns with certain strands of existing research that suggest calendar anomalies might be less prevalent in specific market segments or may experience periods of dormancy. However, the second time period (2016-2023) presents a compelling departure from this pattern, highlighting the dynamic landscape of financial markets.  A statistically significant (p-value 0.05) and persistent anomaly arises, with Tuesdays consistently demonstrating the highest average daily returns within the NIFTY Energy Sector. This observation challenges traditional notions of day-of-the-week effects and necessitates a nuanced exploration of its potential drivers.